(untitled) (International Journal of Food and Nutritional Sciences, 2022)
An outlook towards people and situations is one of the key elements that influence an individual’s professional as well as personal life. In the same way, a teacher’s performance and effectiveness inside the classroom are directly related to his perspective on the job. The success and effectiveness of a teacher are also significantly influenced by his perspective on the job. According to literary definitions, attitude is "the core of human individuality," "the enduring organization of an individual’s inspirational emotional, and cognitive procedures regarding a moment or an intellectual object," "positive or negative in value sensuous intensity," "absorbed tendency," (Fishbein and Ajzen, 1975; Muller, 1986; Tezbaaran, 1997; Bohner and Wanke, 2002). "Probably not becoming recruited" is the aspiring teachers’ top priority when it comes to the future of their profession. They believe their education has certain flaws, which makes them want to become instructors. In order to clarify the objectives, qualitative research using a closed-ended questionnaire was conducted on 68 teachers in order to assess their attitudes about their job. The results demonstrate that the teaching profession offers opportunities for professional development and for taking on job responsibilities.